Hegemony of Power in the Film “Cairo Conspiracy” by Tarik Saleh (Antonio Gramsci’s Theory of Hegemony) - Naufal Adya Wijaya; Rohanda Rohanda; Ihin Solihin (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This research analyzes the representation of hegemony of power in Tarik Saleh's 2022 film "Cairo Conspiracy". This film offers a complex narrative that highlights the dynamics of power, religion and Egyptian politics. Through qualitative analysis using Antonio Gramsci's theory of hegemony of power, this research aims to reveal how the film depicts an unbalanced power relationship between the state, religious institutions, and individuals. Based on his consent and coercion, the analysis focuses on a young man named Adam, who comes from the village of Manzala, and how the hegemony of state power manipulates religious institutions to maintain its dominance. Using the descriptive analytical method, this research concludes that the film "Cairo Conspiracy" exposes the practice of hegemony of power in Egypt's religious political system. The results of this research will be in the form of several points of consent or coercion, namely agreement on domination or coercion, and in this research, there are 13 data that have been analyzed, one example of which is political hegemony which in this film is coercive or forced.